Celebrate with Kim-Joy : cute cakes and bakes to make every occasion joyful - Kim-Joy, 1991- (Hardie Grant/Quadrille, 2021)
"Let Kim-Joy and her signature cuteness brighten your celebrations. From birthday cakes to year-round events, all occasions are covered! The 60 sweet recipes are bursting with colour, imagination and fun and there's something for everyone, no matter what their baking skills. Big occasions include birthdays, Valentine's Day, Halloween, Christmas, weddings; and there are plenty of other celebrations too - Graduation Day, New Year's, new baby, Pride, Thanksgiving, Day of the Dead, Pancake Day and many more. Vegan and gluten-free alternatives are provided so that no one needs to miss out! This joyful collection of recipes includes all the step-by-step photography, clear instructions and words of positivity you need to learn to bake and decorate just like Kim-Joy"--Publisher's description